Causes, Types and Management of Fracture of Dentate Region of Mandible - Ahsan Iqbal, Asif Nazir, Tania Rashid, Saima Sultan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The mandible fracture ranks as the second most often occurring facial fracture. The advent of high-speed automobiles has led to a significant increase in the frequency of accidents in recent times. Mandibular fractures are observed as a notable occurrence of maxillofacial trauma in the region of Multan. Purpose: To determine the Causes, types and management of fracture of dentate region of mandible fracture. Method: The present research is an observational and descriptive investigation including a sample of 52 patients diagnosed with mandible fractures. The study was done at the Nishter Institute of Dentistry in Multan, Pakistan, spanning from September 2021 to February 2023. Following the endorsement of the research by the Ethical Review Board of the hospital, patients were recruited using a non-probability sequential sampling method. This research included patients who had a history of trauma and were admitted to Nishter Institute of Dentistry in Multan, Pakistan, as well as those from the surrounding districts of Multan. The assessment of mandibular fractures included doing extra-oral and intra-oral clinical evaluations, as well as obtaining panoramic and posterior-anterior radiographs of the mandible to establish a diagnosis. The data collected was then subjected to statistical analysis. Result: Among the sample of 52 individuals diagnosed with mandibular fractures, the age group of 21-30 years had the greatest proportion, with a notable male preponderance. The leading causes of fractures were road traffic accidents and assault, with the parasymphysis being the most often affected anatomical region. The occurrence and aetiology of mandibular fracture are indicative of the prevailing trauma patterns in a given population and may serve as a valuable resource for informing the development of initiatives aimed at mitigating and managing such injuries. Conclusions: Patients in the older age (51 years and over) exhibited a higher prevalence of fracture sites in comparison to patients in the younger age. This observation might perhaps be ascribed to the presence of a larger tooth-to-bone ratio. As a result, a decrease in bone density was seen among participants in the younger age category, whereas those in the older age category exhibited an elevation in bone frailty Keywords: Dentate fracture, mandible, trauma